Comparison of bio-clogging characteristics of geotextiles in MSW and bottom ash co-disposal landfills. (1st February 2021) - Wang, Qian; Ko, Jae Hac; Xu, Qiyong
Graphical abstract: Highlights: Bio-clogging was characterized in MSW and bottom ash (BA) co-disposal landfills. Biofilms in the BA landfill showed more diverse than that in the MSW landfill. The BA co-disposal landfill had higher percentage of live cells in bio-clogging. Higher amount of EPS was found in the BA co-disposal landfill. Abstract: Bio-clogging of geotextile is a big challenge for the leachate collection system in landfills. It is important to understand the characteristics of geotextile bio-clogging to develop control technologies. This study investigated the characteristics of geotextile bio-clogging in municipal solid waste landfill (MSW_G) and bottom ash (BA) co-disposal landfill (BA_G). Results showed that the bio-clogging mass of per area in MSW_G and BA_G was 49 ± 5 g/m 2 and 57 ± 3 g/m 2, respectively. Bio-clogging was dominated by live cells in both MSW_G and BA_G. The confocal laser scanning microscopy images revealed that live cells percentage was 46% in MSW_G, while it increased to 77% in BA_G. In contrast, the percentage of the dead cells was 47% and 9% in MSW_G and BA_G, respectively. The biofilm formed in BA _G was thinner and denser than that in MSW_G. Based on the microbial analysis, the biofilms of BA_G had a higher genetic amount and diversity than these of MSW_G. The total amount of extracellular polymeric substances in BA_G was 45.29 ± 4.52 mg/g volatile suspended solids, which was 1.5 times of that in MSW_G. The co-disposal of BA increased the microbial diversity and accelerated bio-clogging due to the high calcium concentration. These findings provide a better understanding of the bio-clogging characteristics, which is helpful to control bio-clogging in co-disposal landfills.